(untitled) (Research, Society and Development, 2022)
The study presents an infometric analysis in relation to the discipline BPM (Business Process Management) applied in the context of public administration. For this, papers published in the last ten years were analyzed, using descriptive statistics in 927 identified articles. The main results were: growth of the terms Business Process Management or BPM and public service or public administration. There was a greater use of these terms in Brazil, the United Kingdom, the Netherlands and the United States. Among the terms mentioned, public administration stood out, with Governance, Business Process management and public management being given importance. With the use of clustering, the words that were most frequently viewed in the titles and in the keywords were: business process management; process management bpm and public administration research. Within the researched universe, it is believed that the scope of BPM emerged as a way to identify opportunities and technological trends, given the lack of knowledge about process analysis, implementation and monitoring.